Strategi Dinas Perindustrian Dan Perdagangan Dalam Pengembangan Usaha Pembuatan Batu Merah Di Kecamatan Bontonompo Kabupaten Gowa - Asmaniar, Nur; Muhammadiah, Muhammadiah; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to determine the role of government was required to play an active role in improving the conditions of the creative industry of red stone crafts so that creative industry could be an alternative in the face of increasingly world market competition. This study used Qualitative with data sources consisting of primary data and secondary data, as many as 9 research informants, data collection techniques were observation and interview guidelines. The results of the study found that the role of the government in the development of local government bricks business was not optimal in playing an active role in paying attention to the group of  Red Stone entrepreneurs in Bontonompo District, this could be seen from the Cost Leadership Strategy, Product Differentiation Strategy and The focus strategy that  more focused on services in the process of developing a red stone manufacturing business in the Bontonompo District, Gowa Regency. Keywords: Strategy, Business Development in the Making of Red Stone